Energy expenditure in the lean and obese - Schoeller, Dale (Henry Stewart Talks, 2009)
History of bioenergetics, Development of the doubly labeled water method, Comparison of total energy expenditure in lean and obese, Components of energy expenditure that explain higher expenditure in the obese, Comparison with data on energy intake, Energy balance and weight gain